Resilient service function chain initial deployment and dynamic replacement towards 6G networks - Deqiang Zhou; Xinsheng Ji; Wei You; Yu Zhao; Hang Qiu; Mingyan Xu (Journal of King Saud University: Computer and Information Sciences)
Abstract Service Function Chain (SFC) enables more facile and convenient composition of on-demand service chains, which can provide customized services for 6G’s six use cases. 6G networks impose higher demands on Quality of Service (QoS), especially with the debut of resilience. Resilience requires that a service can anticipate, withstand, recover from, and adapt to attacks, thereby ensuring the basic function of the service. However, existing works cannot provide the capabilities required for resilience. In our previous work, we designed a Dynamic Heterogeneous Redundant SFC (DHRSFC) to endow SFC with resilience and theoretically proved its excellent ability. Nevertheless, during service provisioning, the initial deployment and dynamic replacement of DHRSFC face significant challenges in ensuring the heterogeneity of DHRSFC and minimizing the impact of redundant SFCs on delay. This is critical to the resilience capability and QoS of DHRSFC. In this article, we propose a hierarchical heterogeneity model to quantify the heterogeneity of DHRSFC. We formulate both the initial deployment and dynamic replacement of DHRSFC as the Resilience-Aware and Delay-Sensitive DHRSFC Initial Deployment (RADSID) problem, which is NP-hard. To solve the RADSID problem, we propose a heuristic algorithm, Greedy k-Shortest Path (GkSP), which can address the initial deployment and SFC dynamic replacement of DHRSFC in an integrated way. Extensive evaluations and comparisons demonstrate the effectiveness of our proposed algorithm. It shows excellent performance in terms of delay and resilience. The proposed algorithm can provide outstanding initial deployment solutions and dynamic replacement solutions for DHRSFC, endowing SFC with the resilience required for 6G.